Morphology and distribution of antennal sensilla in egg parasitoid, Ooencyrtus nezarae (Hymenoptera: Encyrtidae). Issue 7 (25th February 2019) - Roh, Gwang Hyun; Lee, Yeon Jeong; Zhu, Junwei J.; Park, Chung Gyoo
Abstract: Morphology of antennal sensilla and their distribution were investigated in adults of Ooencyrtus nezarae, an egg parasitoid of Riptortus pedestris, using scanning electron microscopy. Male antennae was found to be significantly greater in overall length than female antennae. The antenna of O. nezarae was composed of the radicula, scape, pedicel, funicle and clava in both sexes, with seven types of sensilla identified: sensillum trichodea; s. finger‐like; s. placoidea; s. chaetica; s. basiconica; s. coeloconica, and s. campaniform. They occur in varying number and distribution along the antennae. Two sensillum types were further categorized into additional subtypes, with two subtypes in s. trichodea and three in s. chaetica. Among all characterized sensilla, s. trichodea subtype 1 and s. placoidea were multiporous, indicating that the primary function of these sensilla is olfactory. Sensillum trichodea was the most abundant sensillum type on the antennae of both sexes. Sexual dimorphism was only observed from the subtype 1 sensilla of s. trichodea in males and the subtype 3 sensilla of s. chaetica in females. The morphological information established in our study may provide useful information for further investigations in sensory physiological function of each morphological type of sensilla and their related behavior in this egg parasitoid. Abstract : Antenna of O. nezarae is composed of the radicula (Ra), scape (Sc), pedicel (Pe), funicle (F) and clava (C) in both sexes. Sexual dimorphism is clearly observed in distributions of s. trichodea subtype 1 (Tr1) and s. chaetica 3 (Ch3).